Total body composition estimated by standing-posture 8-electrode bioelectrical impedance analysis in male wrestlers - Cheng, M-F; Chen, Y-Y; Jang, T-R; Lin, W-L; Chen, J; Hsieh, K-C (Biology of Sport, 2016)
Standing-posture 8-electrode bioelectrical impedance analysis is a fast and practical method for evaluating body composition in clinical settings, which can be used to estimate percentage body fat (BF%) and skeletal muscle mass in a subject’s total body and body segments. In this study, dual-energy X-ray absorptiometry (DXA) was used as a reference method for validating the standing 8-electrode bioelectrical impedance analysis device BC-418 (BIA8, Tanita Corp., Tokyo, Japan). Forty-eight Taiwanese male wrestlers aged from 17.9 to 22.3 years volunteered to participate in this study. The lean soft tissue (LST) and BF% in the total body and body segments were measured in each subject by the BIA8 and DXA. The correlation coefficients between total body, arm, leg segments impedance index (BI, ht2/Z) and lean soft tissue mass measured from DXA were r = 0.902, 0.453, 0.885, respectively (p < 0.01). In addition, the total body and segmental LST estimated by the BIA8 were highly correlated with the DXA data (r = 0.936, 0.466, 0.886, p 0.820, p < 0.01). The estimated LST and BF% from BIA8 in the total body and body segments were highly correlated with the DXA results, which indicated that the standing-posture 8-electrode bioelectrical impedance analysis may be used to derive reference measures of LST and BF% in Taiwanese male wrestlers.